Accuracy of ventricular volume estimation. - Wyper, D J (1979)
Sources of error in the estimation of ventricular volume from CAT scans are discussed and the accuracy of the measurement assessed. Two methods of calculating ventricular volume from an intraventricular injection of radioisotope are described and compared. Finally, the CAT scan and isotope methods are compared and contrasted. The error associated with a single measurement of volume by any of these techniques is between 20% and 30%. In patients with no ventricular catheter there is no choice other than to use CAT scanning, but if intraventricular injection is possible this method offers a potentially more accurate volume determination because of his higher signal-to-noise ratio.